Integrated surface/subsurface permafrost thermal hydrology: Model formulation and proof‐of‐concept simulations. Issue 8 (11th August 2016) - Painter, Scott L.; Coon, Ethan T.; Atchley, Adam L.; Berndt, Markus; Garimella, Rao; Moulton, J. David; Svyatskiy, Daniil; Wilson, Cathy J.
Abstract: The need to understand potential climate impacts and feedbacks in Arctic regions has prompted recent interest in modeling of permafrost dynamics in a warming climate. A new fine‐scale integrated surface/subsurface thermal hydrology modeling capability is described and demonstrated in proof‐of‐concept simulations. The new modeling capability combines a surface energy balance model with recently developed three‐dimensional subsurface thermal hydrology models and new models for nonisothermal surface water flows and snow distribution in the microtopography. Surface water flows are modeled using the diffusion wave equation extended to include energy transport and phase change of ponded water. Variation of snow depth in the microtopography, physically the result of wind scour, is modeled phenomenologically with a diffusion wave equation. The multiple surface and subsurface processes are implemented by leveraging highly parallel community software. Fully integrated thermal hydrology simulations on the tilted open book catchment, an important test case for integrated surface/subsurface flow modeling, are presented. Fine‐scale 100 year projections of the integrated permafrost thermal hydrological system on an ice wedge polygon at Barrow Alaska in a warming climate are also presented. These simulations demonstrate the feasibility of microtopography‐resolving, process‐rich simulations as a tool to help understand possible future evolution of the carbon‐rich Arctic tundra in a warming climate. Key Points: New permafrost thermal hydrology simulation capability is available in open‐source parallel software The ATS software combines new surface and subsurface process representations in three dimensions Decadal projections of permafrost dynamics in a warming climate demonstrate the new capability